Association between prevalence of work-related musculoskeletal disorders and work-related ergonomic factors of special education teachers in Kota Bharu, Kelantan/ Nur Atikah Mohamad Adnan and Mohd Suleiman Murad - Mohamad Adnan, Nur Atikah; Murad, Mohd Suleiman (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Work-related musculoskeletal disorders (WMSDs) have become increasingly common among health-related professionals, including special education personnel who serve students with disabilities; however, WMSDs have been overlooked in this population. This study was conducted to investigate the association between the prevalence of WMSDs and work-related ergonomic factors among special education teachers in Kota Bharu, Kelantan. WMSDs questionnaires with three domains were used in this cross-sectional study involving 103 special education teachers. Result: Approximately 72% of the 103 special education teachers experienced musculoskeletal disorders. The lower back, shoulder and neck were the three most affected regions. Results revealed that assisting in diaper changing (p=0.011) and toileting (p=0.007), having no teaching partners (p=0.046), no nap habit (p=0.001) and duration of working experience >5 years (p=0.001), were strongly associated with the prevalence of WMSD. The present study revealed an association between WMSDs and work-related ergonomic factors among special education teachers. Future efforts should emphasize on measure to reduce high prevalence of WMSDs among this group, in order to improve their health status and avoid harmful impact on their personal and working productivity.